PHYTOCHEMICAL AND PHARMACOLOGICAL STUDY OF EHRETIA MICROPHYLLA (BORAGINACEAE FAMILY) BY USING GC-MS - Sain, Shweta; Mishra, Manjul (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The present examination is about the primary investigation and the compound constituent of Boraginaceae species, Ehretia microphylla, by the utilization of GC-MS. Qualitative assessment of Ehretia microphylla by the utilization of GCMS affirmed the presence of eleven selective phytochemical compounds.The leaf phase of the plant was once analysed by way of GC SHIMADZU, model no. GCMS-QP2010 and software program GCMS solution version 4.45 SP1. The GC SHIMADZU utilized in the examination utilized a section loaded with elite 5MS and the factors have been separated by the usage of helium (1mL/min) as the service gas. The compounds were identified by evaluating their maintenance duration and fragmentation patterns with the records saved in the NIST library. The stated main constituent is gamma-sitosterol,13-Docosenamide, and Benzoic acid,4-ethoxy-, ethyl ester.